Memorial Church in Gornji Adrovac as a Symbol of Serbo-Russian Cultural, Political, National, and Artistic Ties in the Late 19th and Early 20th Century - Kostić, Ana D.; Rakonjac, Teodora D. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
During the Serbo-Turkish wars (1876–1878), a Russian volunteer, Colonel Nikolaj Nikolajevich Raevsky, died in a battle at Golo Brdo, the place near the village Gornji Adrovac. One of the monuments built in his honour is a memorial church erected in the place where he was shot. This paper discusses the erection of the memorial church in light of the political circumstances and the national ties between Russia and Serbia during the second half of the 19th and the beginning of the 20th century. The Church in Gornji Adrovac itself stands as a representation of good political, national, and religious ties between Serbia and Russia, as well as an example of artistic transfer and aesthetical ideal in the religious art of the time.